Biodegradable and recoverable non-toxic coating composition
The defects of existing coatings in anti-adhesion, durability and recyclability are solved by using compositions of microcrystalline cellulose, silane and acid catalysts in sol-gel coatings, achieving human health and the environment Harmless waterproof, oilproof and anti-stick effect.
Patent Information
- Application Number
- CN202380044480.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-06-01
- Publication Date
- 2025-02-25
AI Technical Summary
The existing sol-gel coatings have defects in their anti-adhesion, durability and recyclability, and the compounds such as silane used are harmful to the environment and human health.
Using a coating composition containing microcrystalline cellulose, silane and acid catalyst, an anti-stick coating is formed by polymerization and vitrification of silanes, combining an inorganic filler and a liquid dispersed phase to ensure waterproof, oilproof and reversible properties of the coating.
It has achieved waterproof, oil-proof and anti-stick coatings that are harmless to human health and the environment, and has good durability and reversibility, and is suitable for coating substrates in contact with water or grease materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Field of the Invention
[0001] The present invention relates to the general technical field of sol-gel type coatings. More specifically, the present invention belongs to the field of ecological, non-toxic and durable coatings. According to specific aspects, the coating of the present invention can have anti-adhesive properties, water resistance and / or oil resistance relative to pressure-sensitive adhesive compositions. Background of the Invention
[0002] Release liners are an important component of release surfaces that are reversibly attached to an adhesive layer. Examples of such surfaces are the non-adhesive (outer) surface of adhesive tapes, supports for stamps or labels, and disposable accessories for food purposes, such as paper cups for cakes.
[0003] In the field of pressure sensitive adhesives, it is often desirable to prepare a product with an adhesive, such as a label or tape, and store the product before use. During storage, it is advantageous to adhere the product with the adhesive to an intermediate surface from which the product must be removed before use. For example, the tape is wound on a reel so that the adhesive surface of one turn of the tape adheres to the non-adhesive surface of the previous turn. In order to unroll the tape before use, the previous turn of the tape and its adhesive must be removed, usually from the inner turn. In another example, a label with an adhesive is often attached to a backing paper with a release surface from which the label must be easily removed before being prepared for use.
[0004] This protective paper or release liner usually has a plastic film or glassine paper. Usually, the release liner has a very thin silane layer or fluorocarbon polymer layer on one or both sides, which acts as a backing to protect the adhesive surface of the tape when it is wound, or to protect the label or stamp when it is reversibly adhered to a support. When a force is applied, the release surface of the liner makes it possible to separate the wound tape, label or stamp from its release surface without any adverse effect on the adhesiveness of the tape, label or stamp.
[0005] In order to provide a backing with release properties, such as a paper support, current coatings are based on several polymers used as release coatings, such as silane networks, copolymers containing silanes, polymers with long alkyl or fluoroalkyl side chains, fluoropolymers and polyolefins. The surface energy of these polymers is lower than that of commonly used pressure-sensitive adhesive (PSA) compositions, which is an important feature of PSA materials.
[0006] The use of sol-gel compositions in one or more than one layer to form a non-stick coating surface is known in the prior art. However, these coating compositions have drawbacks in terms of durability and non-stick properties.
[0007] In order to overcome these drawbacks, anti-adhesive compositions that also contain silicone oil-type lubricants have been proposed to improve their anti-adhesive properties. However, these silicone oils have limited heat resistance and it is always observed that the anti-adhesive properties of the coatings decrease with use.
[0008] Furthermore, the above-mentioned silicone oil-containing coating compositions according to the prior art are used in the form of an emulsion bath (or coating bath) for coating a film support and then crosslinked under thermal activation and / or radiation (UV, electron beam) to form a water-resistant and anti-stick coating, which hinders the easy implementation of surface coating.
[0009] It is also known to add fluorinated silanes or complex synthetic polymers to sol-gel type coatings to improve their non-stick properties. However, the use of fluorinated compounds may be harmful to human health and the environment, since the presence of fluorinated compounds and high molecular weight synthetic polymers may prevent biodegradation and recycling of materials coated with compositions comprising such fluorinated silanes and / or such complex synthetic polymers.
[0010] Such solutions are therefore not sustainable since they involve the use of compounds that limit the recyclability and / or biodegradability of the PSA non-stick coating.
[0011] Therefore, there remains a need to provide release coating compositions involving PSA adhesives, particularly for surfaces, such as surfaces of food or beverage accessories, that may overcome the above-mentioned disadvantages. In addition, given the practicality of such coatings in food or beverage utensils, there remains a need to provide safe coatings that impart water and oil barrier properties to coated substrates.
[0012] The purposes of coating composition as described below can realize simple coating, and this coating can provide coating products harmless to human health or environment.Advantageously, this coating has the isolation property that prevents water and / or grease diffusion, and is applicable to the coating substrate that contacts with water or grease material, for example food or beverage container.According to still advantageous aspect, coating composition according to the present invention has reversible adhesion, and this property is under the force that user usually applies, and is usually the force of the order of magnitude of 1g / cm to 500g / cm, for example, in order to open disposable food container or stamp is removed from its support, and this coating composition is non-adhesive.More advantageously, no matter how temperature or humidity, the reversibility of the non-adhesive nature of composition all can persist over time.In addition, composition according to the present invention can not diffuse into the substrate that it applies, and can not diffuse into the adhesive layer that contacts with it. SUMMARY OF THE INVENTION
[0013] The present invention relates to a coating composition comprising:
[0014] - a cellulose composition in an amount ranging from 0.1% to 15% by weight relative to the total weight of the coating composition, wherein the cellulose is selected from microcrystalline cellulose, microfibrillated cellulose and mixtures thereof,
[0015] - at least one silane in an amount of 50% to 80% by weight relative to the total weight of the coating composition,
[0016] - at least one acid catalyst in an amount ranging from 0.05% to 5.0% by weight relative to the total weight of the composition,
[0017] - optionally at least one inorganic filler, and
[0018] - a liquid dispersed phase in an amount sufficient to bring the total weight of the coating composition to 100%.
[0019] The at least one silane may be selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane, trimethoxysilane, triethoxysilane and mixtures thereof. Preferably, the at least one silane is selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, even more preferably, the at least one silane is methyltriethoxysilane.
[0020] When the coating composition further comprises at least one inorganic filler (or filler), it may be selected from silicon dioxide, calcium carbonate, magnesium carbonate, aluminum oxide, layered silicate, linear silicate, framework silicate, talc, zinc sulfate, magnesium oxide, zinc flake, kaolin, albarin, dolomite, cerium oxide, sodium aluminate, calcium sulfate, barium sulfate, zinc stearate and mixtures thereof, preferably, the at least one inorganic filler is selected from silicon dioxide, calcium carbonate and mixtures thereof, even more preferably, the at least one inorganic filler is silicon dioxide, in particular micronized silicon dioxide.
[0021] The at least one acid catalyst may be selected from monoprotic acids, preferably also selected from hydrochloric acid, nitric acid and acetic acid; and polyprotic acids, preferably also selected from carbonic acid, sulfuric acid and citric acid and mixtures thereof; even more preferably the acid catalyst is hydrochloric acid.
[0022] In certain embodiments, the coating composition comprises a cellulose composition that is a microcrystalline cellulose composition having crystals having an average diameter of 30 μm to 200 μm, as determined by sieving.
[0023] In certain embodiments, the dispersed phase is an aqueous phase or an aqueous-alcoholic phase, preferably the dispersed phase is 100% water.
[0024] In certain embodiments, the coating composition comprises:
[0025] - a microcrystalline cellulose composition, preferably in an amount ranging from 1% to 15% by weight relative to the total weight of the composition, preferably from 1% to 5% by weight, even more preferably having crystals with an average diameter ranging from 30 μm to 200 μm, the average diameter being determined by sieving.
[0026] - at least one silane, preferably in an amount of 60% to 80% by weight relative to the total weight of the coating composition, even more preferably the at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, more preferably the at least one silane is methyltriethoxysilane;
[0027] - at least one acid catalyst, preferably in an amount ranging from 1.0% to 5.0% by weight relative to the total weight of the composition;
[0028] - optionally at least one inorganic filler, preferably in an amount ranging from 0.1% to 10% by weight relative to the total weight of the composition, even more preferably said at least one inorganic filler being chosen from silica, calcium carbonate and mixtures thereof; and
[0029] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%.
[0030] In certain embodiments, the coating composition comprises:
[0031] - a microfibrillated cellulose composition, preferably in an amount ranging from 1% to 15% by weight, preferably from 1% to 5% by weight relative to the total weight of the composition;
[0032] - at least one silane, preferably in an amount of 60% to 80% by weight relative to the total weight of the composition, even more preferably said at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, more preferably said at least one silane is methyltriethoxysilane;
[0033] - at least one acid catalyst, preferably in an amount ranging from 1.0% to 5.0% by weight relative to the total weight of the composition;
[0034] - optionally at least one inorganic filler, preferably in an amount ranging from 0.1% to 10% by weight relative to the total weight of the composition, even more preferably said at least one inorganic filler being chosen from silica, calcium carbonate and mixtures thereof; and
[0035] - a liquid dispersed phase, preferably 100% water, in an amount sufficient to bring the total composition to 100%.
[0036] The present invention also relates to the use of a coating composition as described herein, wherein the substrate is a cellulose-containing substrate, or wherein the substrate is a plastic substrate or a metal substrate, preferably the substrate is a cellulose-containing substrate comprising at least 70 wt.-% cellulose relative to the total weight of the substrate.
[0037] In certain embodiments, the coating is a release coating, preferably a release coating configured to reversibly adhere to an adhesive surface, such as a layer comprising acrylates and / or polyacrylates.
[0038] Alternatively or additionally, the coating is a water- and / or oil-repellent coating of a cellulosic substrate.
[0039] The present invention also relates to a composite article comprising a substrate at least partially coated with a coating composition as described herein.
[0040] Typically, the substrate of the composite article comprises at least 70% by weight of cellulose relative to the total weight of the substrate.
[0041] Alternatively, the substrate comprises or consists of metal or plastic.
[0042] In certain embodiments, the composite article is selected from food items, preferably disposable food items, food protection papers, cardboard containers for food, disposable tableware, paper containers, paper cups, tapes, supports for stamps or labels, molds for food cooking, in particular molds for cakes or metal molds for injection molding. definition
[0043] In the present invention, the following terms have the following meanings:
[0044] "Anti-stick coating" or "release coating" refers to a coating that can reversibly adhere (adhere) to an adhesive layer. Reversible adhesion means that the adhesion of an adhesive layer, especially a pressure-sensitive adhesive (PSA) layer, to a release liner is reversible when a separation (or peeling) force exceeding a threshold value is applied, the threshold value being greater than or equal to 1 g / cm, greater than or equal to 5 g / cm, preferably greater than or equal to 10 g / cm, even more preferably greater than or equal to 12 g / cm or 15 g / cm, while the adhesive layer retains its adhesiveness after being separated from the release coating. DETAILED DESCRIPTION OF THE INVENTION
[0045] In a first aspect, the present invention is directed to a composition comprising: a microcrystalline cellulose composition, at least one silane, at least one acid catalyst, and a liquid dispersed phase.
[0046] In particular, the coating composition of the present application comprises:
[0047] - a cellulose composition in an amount ranging from 0.1% to 15% by weight, preferably from 1% to 15% by weight, more preferably from 1% to 5% by weight, relative to the total weight of the coating composition, wherein the cellulose is selected from microcrystalline cellulose, microfibrillated cellulose and mixtures thereof;
[0048] - at least one silane in an amount of 50% to 80% by weight relative to the total weight of the coating composition;
[0049] - at least one acid catalyst in an amount ranging from 0.05% to 5.0% by weight relative to the total weight of the composition;
[0050] - optionally at least one inorganic filler; and
[0051] - a liquid dispersed phase in an amount sufficient to bring the total weight of the coating composition to 100%.
[0052] The composition according to the invention comprises at least one silane in an amount ranging from 50% to 80% by weight, preferably from 60% to 80% by weight, even more preferably from 60% to 70% by weight, relative to the total weight of the composition.
[0053] In one embodiment, the at least one silane is selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane, trimethoxysilane, triethoxysilane and mixtures thereof, preferably the at least one silane is selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane, and mixtures thereof, more preferably, the at least one silane is methyltriethoxysilane.
[0054] In certain embodiments, the composition further comprises at least one inorganic filler.
[0055] When the composition according to the invention comprises at least one inorganic filler, the amount of inorganic filler may range from 0.05% to 20% by weight, preferably from 0.1% to 10% by weight, even more preferably from 1% to 5% by weight relative to the total weight of the composition.
[0056] The inorganic filler can be selected from silicon dioxide, calcium carbonate, magnesium carbonate, aluminum oxide, layered silicate, linear silicate, framework silicate, talc, zinc sulfate, magnesium oxide, zinc flake, kaolin, albarin, dolomite, cerium oxide, sodium aluminate, calcium sulfate, barium sulfate, zinc stearate and mixtures thereof. Preferably, the at least one inorganic filler is selected from silicon dioxide, calcium carbonate and mixtures thereof. More preferably, the at least one inorganic filler is micronized silicon dioxide.
[0057] In a preferred embodiment, the inorganic filler is silicon dioxide, preferably in micronized form. Micronized silicon dioxide typically comprises silicon dioxide particles having an average diameter of 2µm to 5µm, typically 2µm to 3µm, as characterized by sieving.
[0058] When the composition is applied to a substrate, the at least one acid catalyst is present in a sufficient amount to polymerize or vitrify the at least one silane. The composition according to the invention comprises at least one acid catalyst in an amount of 0.01% to 5% by weight, preferably 0.05% to 5% by weight, even more preferably 0.2% to 1% by weight relative to the total weight of the composition.
[0059] At least one acid catalyst can be selected from monoprotic acid, polyprotic acid and mixtures thereof. Preferably, the monoprotic acid is selected from carbonic acid, sulfuric acid and citric acid and mixtures thereof. In one embodiment, the monoprotic acid is selected from hydrochloric acid, nitric acid and acetic acid. In a preferred embodiment, the acid catalyst is hydrochloric acid. Therefore, in certain embodiments, at least one acid catalyst is hydrochloric acid in an amount of 0.01% to 5% by weight relative to the total weight of the composition, preferably 0.05% to 5% by weight, and even more preferably 0.2% to 1% by weight.
[0060] The composition according to the present invention comprises at least one cellulose composition in an amount of 0.1% to 15% by weight, preferably 1% to 15% by weight or 0.5% to 10% by weight, even more preferably 1% to 5% by weight, relative to the total weight of the composition. The cellulose composition is selected from microcrystalline cellulose compositions, microfibrillated cellulose compositions and mixtures thereof.
[0061] In some embodiments, the cellulose composition is a microcrystalline cellulose composition. Microcrystalline cellulose (MCC) is a natural polymer composed of glucose units connected by 1-4β glycosidic bonds. Typically, the microcrystalline cellulose composition has crystals with an average diameter of 30μm to 200μm, and the average diameter is determined by sieving. In one embodiment, the microcrystalline cellulose composition has crystals with an average diameter of 5μm to 200μm, preferably 30μm to 200μm, even more preferably 60μm to 150μm, and the average diameter is determined by sieving. In one embodiment, the microcrystalline cellulose composition has crystals with an average diameter of 60μm to 100μm. In certain embodiments, the coating composition of the present invention comprises an MCC composition, and the amount of the MCC composition is 0.1% to 15% by weight relative to the total weight of the coating composition, preferably 1% to 15% by weight or 0.5% to 10% by weight, and even more preferably 1% to 5% by weight.
[0062] In certain embodiments, the cellulose composition is a microfibrillated cellulose (MFC) composition. Microfibrillated cellulose is a cellulose-based product, described in, for example, the application of US 4 374 702. Compared with non-fibrillated cellulose, microfibrillated cellulose has at least one reduced length scale (diameter, fiber length). In (non-fibrillated) cellulose, which is the starting product for producing microfibrillated cellulose, there is no, or at least no large amount, or even no obvious part of single and "separated" cellulose "fibrils" can be found. The cellulose in the fiber is an aggregate of fibrils. Typical cellulose fibrils aggregate into microfibrils, which further aggregate into larger fibril bundles to eventually form cellulose fibers. The diameter of cellulose fibers is typically 10µm to 50µm (the length of these fibers is even greater than 50µm). When cellulose fibers are microfibrillated, a heterogeneous mixture of "anti-sticking" fibrils with cross-sectional dimensions and lengths ranging from nm to µm may be produced. Fibrils and fibril bundles can coexist in the resulting microfibrillated cellulose.
[0063] In an exemplary embodiment of the invention, the microfibrillated cellulose has a reduction in at least one length scale, i.e. the fibril diameter and / or the fibril length, relative to the fiber diameter and / or the fiber length of the non-fibrillated cellulose; preferably, wherein the diameter of the microfibrillated cellulose fibrils constituting the microfibrillated cellulose of the invention is in the nanometer range. i.e. 1 nm to 1000 nm, preferably and on average 10 nm to 500 nm. Individual fibrils or fibril bundles can be identified and easily determined by any method known in the art, for example by conventional optical microscopy, for example magnified 40 times.
[0064] In certain embodiments, the coating composition of the present invention comprises an MFC composition, and the amount of the MFC composition is 0.1 wt % to 15 wt %, preferably 1 wt % to 15 wt % or 0.5 wt % to 10 wt %, and even more preferably 1 wt % to 5 wt %, relative to the total weight of the coating composition.
[0065] The above components can be dispersed in any dispersed phase known in the art. In one embodiment, the dispersed phase is an aqueous phase or a hydroalcoholic phase. In one embodiment, the hydroalcoholic phase consists of water and at least one short-chain alcohol, i.e., a C1 to C4 chain alcohol, the amount of the short-chain alcohol being at least 5 wt %, at least 10 wt %, at least 20 wt % or at least 30 wt % relative to the total weight of the hydroalcoholic phase. For example, the at least one short-chain alcohol is selected from ethanol, methanol, isopropanol, butanol and mixtures thereof.
[0066] The amount of dispersed phase is usually sufficient to disperse the ingredients of the composition. According to a variant, the dispersed phase is a sufficient amount (QSP) such that the total weight of the coating composition reaches 100%. Typically, the amount of dispersed phase is 15% to 40% by weight relative to the total weight of the composition. According to a variant, in the case where the dispersed phase of the ingredients constitutes the dispersed phase of the composition according to the invention, the ingredients of the composition, such as microcrystalline cellulose and / or inorganic filler, are in the form of a suspension in its dispersed phase.
[0067] In a preferred embodiment, the dispersed phase is 100% water.
[0068] According to certain embodiments, the coating composition comprises:
[0069] - a cellulose composition, preferably in an amount of 1% to 15%, even more preferably 1% to 5%, wherein the cellulose is selected from microcrystalline cellulose, microfibrillated cellulose and mixtures thereof;
[0070] - at least one silane as described above, preferably in an amount of 50% to 80%, preferably 60% to 80%, even more preferably 60% to 70%;
[0071] - at least one acid catalyst, as described above, in an amount sufficient to polymerize said at least one silane, preferably in an amount of 0.01% to 5%, preferably 0.05% to 5.0%, more preferably 0.2% to 1%; and
[0072] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, generally ranging from 15% to 40%;
[0073] The percentages are expressed by weight relative to the total weight of the composition.
[0074] According to certain embodiments, the coating composition comprises:
[0075] - a cellulosic composition selected from MCC, MFC or a combination thereof, preferably in an amount of 1% to 15%, even more preferably 1% to 5%;
[0076] - at least one silane as described above, preferably in an amount of 50% to 80%, preferably 60% to 80%, even more preferably 60% to 70%; preferably, the at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, even more preferably, the at least one silane is methyltriethoxysilane;
[0077] - at least one acid catalyst, preferably hydrochloric acid, in an amount sufficient to polymerize the at least one silane, preferably in an amount of 0.01% to 5%, preferably 0.05% to 5.0%, more preferably 0.2% to 1%; and
[0078] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, generally ranging from 15% to 40%;
[0079] The percentages are expressed by weight relative to the total weight of the composition.
[0080] According to certain embodiments, the coating composition comprises:
[0081] - microcrystalline cellulose composition, preferably in an amount of 1% to 15%, even more preferably 1% to 5%; more preferably the microcrystalline cellulose composition has crystals with an average diameter of 5µm to 200µm, 30µm to 200µm, 60µm to 200µm, preferably 60µm to 150µm, more preferably 60µm to 100µm, the average diameter being determined by sieving;
[0082] - at least one silane as described above, preferably in an amount of 50% to 80%, preferably 60% to 80%, even more preferably 60% to 70%; preferably, the at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, even more preferably, the at least one silane is methyltriethoxysilane;
[0083] - at least one acid catalyst, preferably hydrochloric acid, in an amount sufficient to polymerize the at least one silane, preferably in an amount of 0.01% to 5%, preferably 0.05% to 5.0%, more preferably 0.2% to 1%; and
[0084] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, generally ranging from 15% to 40%;
[0085] The percentages are expressed by weight relative to the total weight of the composition.
[0086] According to certain embodiments, the coating composition comprises:
[0087] - microcrystalline cellulose composition, preferably in an amount of 1% to 15%, even more preferably 1% to 5%; more preferably the microcrystalline cellulose composition has crystals with an average diameter of 5µm to 200µm, 30µm to 200µm, 60µm to 200µm, preferably 60µm to 150µm, more preferably 60µm to 100µm, the average diameter being determined by sieving;
[0088] - at least one silane as described above, preferably in an amount of 50% to 80%, preferably 60% to 80%, even more preferably 60% to 70%; preferably, the at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, even more preferably, the at least one silane is methyltriethoxysilane;
[0089] - at least one acid catalyst, preferably hydrochloric acid, in an amount sufficient to polymerize the at least one silane, preferably in an amount of 0.01% to 5%, preferably 0.05% to 5.0%, more preferably 0.2% to 1%;
[0090] - at least one inorganic filler, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, even more preferably said at least one inorganic filler is silicon dioxide, in particular micronized silicon dioxide, and
[0091] - a sufficient amount of a liquid dispersed phase, preferably in an amount of 15% to 40%, even more preferably the dispersed phase is 100% water;
[0092] The percentages are expressed by weight relative to the total weight of the composition.
[0093] In certain embodiments, the coating composition comprises:
[0094] - a microcrystalline cellulose composition, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, even more preferably, said microcrystalline cellulose composition having crystals with a mean diameter ranging from 60 µm to 150 μm, as determined by sieving;
[0095] - at least one silane, preferably in an amount of 60% to 70%, the at least one silane being selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, preferably the at least one silane is methyltriethoxysilane;
[0096] - at least one acid catalyst, preferably hydrochloric acid, more preferably in an amount ranging from 0.2% to 1.0% by weight relative to the total weight of the composition;
[0097] - at least one inorganic filler, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, said at least one inorganic filler being chosen from calcium carbonate, silicon, in particular micronized silicon dioxide, and mixtures thereof, more preferably said at least one inorganic filler being silicon dioxide, in particular micronized silicon dioxide, and
[0098] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, in an amount ranging from 15% to 40%, even more preferably the dispersed phase is 100% water;
[0099] The percentages are expressed by weight relative to the total weight of the composition.
[0100] In certain embodiments, the coating composition comprises:
[0101] - a cellulose composition chosen from an MCC composition or an MFC composition, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition;
[0102] - at least one silane, preferably in an amount of 60% to 70%, the at least one silane being selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, preferably the at least one silane is methyltriethoxysilane;
[0103] - at least one acid catalyst, preferably hydrochloric acid, more preferably in an amount ranging from 0.2% to 1.0% by weight relative to the total weight of the composition;
[0104] - at least one inorganic filler, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, said at least one inorganic filler being chosen from calcium carbonate, silicon, in particular micronized silicon dioxide, and mixtures thereof, more preferably said at least one inorganic filler being silicon dioxide, in particular micronized silicon dioxide, and
[0105] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, in an amount ranging from 15% to 40%, even more preferably the dispersed phase is 100% water;
[0106] The percentages are expressed by weight relative to the total weight of the composition.
[0107] In certain embodiments, the coating composition comprises:
[0108] - a microcrystalline cellulose composition, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, even more preferably having crystals with an average diameter ranging from 60 µm to 150 μm, determined by sieving.
[0109] - at least one silane, preferably in an amount of 60% to 70%, the at least one silane being selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, preferably the at least one silane is methyltriethoxysilane;
[0110] - at least one acid catalyst, preferably hydrochloric acid, more preferably in an amount ranging from 0.2% to 1.0% by weight relative to the total weight of the composition;
[0111] - at least one inorganic filler, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, said at least one inorganic filler being chosen from calcium carbonate, silicon, in particular micronized silicon dioxide, and mixtures thereof, more preferably said at least one inorganic filler being silicon dioxide, in particular micronized silicon dioxide, and
[0112] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, in an amount ranging from 15% to 40%, even more preferably the dispersed phase is 100% water;
[0113] The percentages are expressed by weight relative to the total weight of the composition.
[0114] In certain embodiments, the coating composition comprises:
[0115] - MFC composition, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition;
[0116] - at least one silane, preferably in an amount of 60% to 70%, the at least one silane being selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, preferably the at least one silane is methyltriethoxysilane;
[0117] - at least one acid catalyst, preferably hydrochloric acid, more preferably in an amount ranging from 0.2% to 1.0% by weight relative to the total weight of the composition;
[0118] - at least one inorganic filler, preferably in an amount ranging from 1% to 5% by weight relative to the total weight of the composition, said at least one inorganic filler being chosen from calcium carbonate, silicon, in particular micronized silicon dioxide, and mixtures thereof, more preferably said at least one inorganic filler being silicon dioxide, in particular micronized silicon dioxide, and
[0119] - a liquid dispersed phase in an amount sufficient to bring the total composition to 100%, in an amount ranging from 15% to 40%, even more preferably the dispersed phase is 100% water;
[0120] The percentages are expressed by weight relative to the total weight of the composition.
[0121] The coating composition of the present invention is suitable for applying a non-stick coating to a substrate as described above, such as a cellulose-containing substrate, a metal substrate or a plastic substrate. In addition, the coating composition of the present invention is suitable for applying a non-stick (anti-) water and / or oil coating to a substrate, such as a cellulose-containing substrate, a metal substrate or a plastic substrate, preferably to a cellulose-containing substrate.
[0122] Thus, in a second aspect, the present invention relates to the use of a coating composition according to any of the previously mentioned embodiments as a coating for a substrate.
[0123] In certain embodiments, the coating is a non-stick coating, a water-resistant (or waterproof) and / or oil-resistant (or oil-resistant or grease-resistant) coating, preferably the coating is a non-stick coating.
[0124] Alternatively, the present invention relates to a method for preparing a non-stick coating, a water-repellent coating and / or an oil-repellent coating, preferably a non-stick coating, which comprises contacting a substrate with a composition according to any one of the above embodiments.
[0125] According to certain embodiments, the use or coating method according to the invention relates to a release coating, in particular a release coating capable of adhering to an adhesive layer in a reversible manner as described above. According to certain other embodiments, the use or coating method according to the invention relates to protection against water or oily (fat or grease) type substances, in particular in the coating of cellulosic substrates for articles for food and / or beverage applications or utensils.
[0126] In certain embodiments, the substrate is a cellulose substrate, a metal substrate or a plastic substrate, preferably the substrate is a cellulose substrate. A cellulose substrate or a cellulose-containing substrate refers to a substrate comprising at least 70% by weight of cellulose relative to the total weight of the substrate. The cellulose-containing substrate can be selected from paper, treated paper, cellophane, paperboard, a cellulose support, a low-pore cellulose support and wood, preferably selected from paper, cellophane and paperboard.
[0127] In certain embodiments, the process of coating a substrate comprises the following steps:
[0128] a) providing a substrate,
[0129] b) providing a coating composition according to the invention, then
[0130] c) applying the coating composition to at least a portion of the substrate, preferably to at least one surface of the substrate, to obtain a preliminary composite article, and then
[0131] d) drying the preliminary composite product at 30°C to 280°C to obtain a coated substrate.
[0132] In certain embodiments, the process comprises the following steps:
[0133] a) providing a substrate selected from a cellulose-containing substrate, a metal substrate or a plastic substrate,
[0134] b) providing a coating composition according to any one of the above embodiments,
[0135] c) applying the coating composition to at least one surface of a substrate to obtain a preliminary composite coated article, and
[0136] d) drying the preliminary composite coated product at a temperature of 20° C. for several days to 280° C. for less than 1 minute to obtain a composite coated product.
[0137] In a third aspect, the invention relates to a composite article comprising a substrate at least partially coated with a coating composition according to the invention. Advantageously, the coating composition according to the invention is capable of reversibly adhering to an adhesive surface, in particular to a pressure-sensitive adhesive layer surface, for example a layer comprising acrylates and / or polyacrylates, such as the adhesive layers present in Loctite® 592, Technomelt® PS, Extra Strong Premium Carpet Tape NIU 4202® sold by Scotch.
[0138] In certain embodiments, the composite article comprises a cellulose, plastic substrate body, or a metal substrate body as described above.
[0139] In certain embodiments, the substrate comprises at least 70 wt% cellulose relative to the total weight of the substrate.In certain embodiments, the body of the substrate comprises, consists essentially of, or consists of metal or plastic.
[0140] In certain embodiments, the coating article is selected from food items, preferably disposable food items, food protection papers, cardboard containers for food, disposable tableware, paper containers, paper cups, tapes, supports for stamps or labels, molds for food cooking, in particular molds for cakes or metal molds for injection molding.
[0141] According to one embodiment, the article is chosen from food articles, in particular disposable food articles, food protection papers, cardboard containers for food, disposable cutlery, adhesive tapes, supports for stamps or labels, moulds for food cooking, in particular moulds for cakes or metal moulds for injection moulding.
[0142] According to a fourth aspect, the present invention relates to a composite coated article comprising:
[0143] - a first layer, which consists of the above-mentioned substrate, which is usually selected from a cellulose-containing substrate, a metal substrate or a plastic substrate, preferably a cellulose-containing substrate, and
[0144] - at least one second layer comprising a coating composition according to any of the above embodiments.
[0145] In one embodiment, a composite coated article is obtainable or directly obtained by coating a substrate with the coating method of the present invention.
[0146] In one embodiment, the composite coated article is a preliminary composite coated article.
[0147] In one embodiment, the composite coating article is a (dried) composite coating article. It should be understood that the drying step (d) removes the dispersed phase of the coating composition. Therefore, the composite coating article comprises:
[0148] - a first layer, which consists of the above-mentioned substrate, which is usually selected from a cellulose-containing substrate, a metal substrate or a plastic substrate, preferably a cellulose-containing substrate, and
[0149] - at least one second layer comprising at least one cellulose (MCC, MFC or a combination thereof) in a silane coating composition as described above condensed by an acid catalyst.
[0150] Therefore, the composite coating product of the present invention can exhibit the release properties as described above and / or keep each liquid portion (water, oil, etc.) inside or outside the package to avoid any contamination or leakage. Example
[0151] The following examples further illustrate the present invention in a non-limiting manner.
[0152] Embodiment 1: Compositions according to the invention
[0153] Compositions A to G according to the present invention were prepared by mixing the ingredients in Table 1.
[0154]
[0155] Table 1 Compositions A to G of the non-stick coating according to Example 1. MCC: microcrystalline cellulose; (d): average diameter of MCC crystals; TEOS: tetraethoxysilane; MTMS: methyltrimethoxysilane; MTES: methyltriethoxysilane, m*SiO2: micronized silicon dioxide.
[0156] The ingredients of composition A to composition G have been mixed for 2 hours to 24 hours (ideally 6 hours to 18 hours). After mixing, the viscosity of composition A to composition G at 25° C. is less than 100 cps.
[0157] The resulting coating composition ("sol" composition) is then applied to a paper substrate to form a release layer.
[0158] A single layer of release coating was applied on A4 paper using a rod coater, with the amount of coating applied ranging from 1ml to 4ml per A4 paper liner (55gsm). The A4 paper liner was made of Prego® paper manufactured by UPM.
[0159] The thus coated paper was then dried in an oven at 150° C. for 30 minutes.
[0160] Example 2: Anti-adhesion Materials and methods
[0161] In order to quantitatively measure the anti-adhesive properties of the composition according to Example 1, we used a dynamic mechanical analyzer from Seiko Instruments.
[0162] A 5 mm x 30 mm rectangular paper sample coated with each of Composition A to Composition G according to Example 1 was prepared and tested in the tension mode of a Seiko® DMS110 dynamic mechanical analyzer console according to the following detailed conditions.
[0163] The samples are:
[0164] - Cool to -30°C and equilibrate at this temperature for 15 minutes (condition 1), then
[0165] -Heat at a rate of 2°C / min to 200°C (Condition 2), then
[0166] - Cool to room temperature (condition 3).
[0167] Condition 4 consisted of maintaining the samples at 38°C and 90% relative humidity for 24 hours.
[0168] This procedure was repeated four times for each sample.
[0169] result
[0170] The results are shown in Table 2.
[0171]
[0172] Table 2
[0173] The samples coated with the compositions A to G of the present invention maintained the reversibility of the non-stick property regardless of the temperature or humidity according to conditions 1 to 4.
[0174] In addition, the anti-stick properties of the Compositions A through G coatings were empirically demonstrated by reversibly adhering commercial adhesives, such as Avery® or 3M® brand adhesive labels, double adhesive carpet tape, and other acrylic or polyacrylate based stickers to samples coated with Compositions A through G.
[0175] Example 3: Oil-Water Repellency and Anti-Adhesion
[0176] The oil and water repellency of the coating compositions of the present invention were evaluated by comparing comparative sol-gel coatings, sol-gels with MCC according to the present invention, and sol-gels with MFC according to the present invention using the TAPPI Cobb 30-minute standard test. The Cobb test is based on the TAPPI 441 test method and measures the amount of water absorbed by non-absorbent paper, paperboard, and corrugated fiberboard in a specified time under standardized conditions. In addition, we performed a release test using FINAT test method 3 and standard adhesive 7475.
[0177] The following test conditions were evaluated:
[0178] (i) Sol-gel standard, 1 layer applied, dry weight 8 gsm
[0179] (ii) Sol-gel MCC, 1 layer applied, dry weight 6 gsm
[0180] (iii) Sol-gel MFC, 1 layer applied, dry weight 5 gsm.
[0181] For the synthesis of (ii), we used 80 µm MCC from Sigma-Aldrich and in the case of MFC-sol-gel (iii), MFC was a commercial grade from Borregaard called Exilva® P 01-V.
[0182] The results are shown in Table 3.
[0183]
[0184] Table 3
[0185] Compared to the standard sol-gel, the sol-gel with MCC and the sol-gel with MFC showed better results in both oil and water Cobb values, and in the FINAT anti-stick test using the standard binder 7475, the sol-gel with MCC and the sol-gel with MFC had almost identical results, in which the standard sol-gel coating did not show any anti-stick properties. This also demonstrates the efficacy and versatility of the coating composition of the present invention.
Claims
1. A coating composition, comprising: - a cellulose composition in an amount ranging from 0.1% to 15% by weight relative to the total weight of the coating composition, wherein the cellulose is selected from microcrystalline cellulose, microfibrillated cellulose and mixtures thereof; - at least one silane in an amount of 50% to 80% by weight relative to the total weight of the coating composition; - at least one acid catalyst in an amount ranging from 0.05% to 5.0% by weight relative to the total weight of the composition; - optionally at least one inorganic filler; and - a liquid dispersed phase in an amount sufficient to bring the total weight of the coating composition to 100%.
2. The coating composition according to claim 1, wherein the at least one silane is selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane, trimethoxysilane, triethoxysilane and mixtures thereof, preferably selected from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, even more preferably, the at least one silane is methyltriethoxysilane.
3. The coating composition according to claim 1 or claim 2, wherein the at least one inorganic filler is selected from the group consisting of silicon dioxide, calcium carbonate, magnesium carbonate, aluminum oxide, layered silicates, linear silicates, framework silicates, talc, zinc sulfate, magnesium oxide, zinc flakes, kaolin, albarin, dolomite, cerium oxide, sodium aluminate, calcium sulfate, barium sulfate, zinc stearate and mixtures thereof, preferably, the at least one inorganic filler is selected from the group consisting of silicon dioxide, calcium carbonate and mixtures thereof, even more preferably, the at least one inorganic filler is silicon dioxide, in particular micronized silicon dioxide.
4. The coating composition according to any one of claims 1 to 3, wherein the at least one acid catalyst is selected from monoprotic acids, preferably also selected from hydrochloric acid, nitric acid and acetic acid; and polyprotic acids, preferably also selected from carbonic acid, sulfuric acid and citric acid and mixtures thereof; even more preferably the acid catalyst is hydrochloric acid.
5. The coating composition according to any one of claims 1 to 4, wherein the dispersed phase is an aqueous phase or a hydroalcoholic phase, preferably the dispersed phase is 100% water.
6. The coating composition according to any one of claims 1 to 5, wherein the cellulose composition is a microcrystalline cellulose composition having crystals with an average diameter of 30 μm to 200 μm, the average diameter being determined by sieving.
7. The composition for a release coating for a substrate according to any one of claims 1 to 6, comprising: - a microcrystalline cellulose composition, preferably in an amount ranging from 1% to 15% by weight, preferably from 1% to 5% by weight relative to the total weight of the composition, even more preferably, said microcrystalline cellulose composition having crystals with a mean diameter ranging from 30 μm to 200 μm, said mean diameter being determined by sieving; - at least one silane, preferably in an amount ranging from 60% to 80% by weight relative to the total weight of the composition, even more preferably said at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, still more preferably said at least one silane is methyltriethoxysilane; - at least one acid catalyst, preferably in an amount ranging from 1.0% to 5.0% by weight relative to the total weight of the composition; - optionally at least one inorganic filler, preferably in an amount ranging from 0.1% to 10% by weight relative to the total weight of the composition, even more preferably said at least one inorganic filler being chosen from silica, calcium carbonate and mixtures thereof; and - a liquid dispersed phase, preferably 100% water, in an amount sufficient to bring the total composition to 100%.
8. The composition for a release coating for a substrate according to any one of claims 1 to 5, comprising: - a microfibrillated cellulose composition, preferably in an amount ranging from 1% to 15% by weight, preferably from 1% to 5% by weight relative to the total weight of the composition; - at least one silane, preferably in an amount ranging from 60% to 80% by weight relative to the total weight of the composition, even more preferably said at least one silane is chosen from methyltriethoxysilane, methyltrimethoxysilane, tetraethoxysilane and mixtures thereof, still more preferably said at least one silane is methyltriethoxysilane; - at least one acid catalyst, preferably in an amount ranging from 1.0% to 5.0% by weight relative to the total weight of the composition; - optionally at least one inorganic filler, preferably in an amount ranging from 0.1% to 10% by weight relative to the total weight of the composition, even more preferably said at least one inorganic filler being chosen from silica, calcium carbonate and mixtures thereof; and - a liquid dispersed phase, preferably 100% water, in an amount sufficient to bring the total composition to 100%.
9. Use of the coating composition according to any one of claims 1 to 8 for coating a substrate, wherein the substrate is a cellulose-containing substrate or wherein the substrate is a plastic substrate or a metal substrate, preferably the substrate is a cellulose-containing substrate comprising at least 70% by weight of cellulose relative to the total weight of the substrate.
10. Use according to claim 9, wherein the coating is a release coating, preferably a release coating configured to reversibly adhere to an adhesive surface, such as a layer comprising acrylates and / or polyacrylates.
11. Use according to claim 9 or claim 10, wherein the coating is a water- and / or oil-repellent coating of a substrate, preferably a cellulose-containing substrate. 12 . A composite article comprising a substrate at least partially coated with the release coating composition for a substrate according to claim 1 .
13. The composite article according to claim 12, wherein the substrate comprises at least 70% by weight of cellulose relative to the total weight of the substrate.
14. The composite article of claim 12, wherein the substrate comprises or is made of metal or plastic.
15. The composite article according to any one of claims 12 to 14, said article being selected from food items, preferably disposable food items, food protection papers, cardboard containers for food, disposable cutlery, paper containers, paper cups, tapes, supports for stamps or labels, moulds for food cooking, in particular moulds for cakes or metal moulds for injection moulding.
Citation Information
Patent Citations
Microfibrillated cellulose
US4374702A